Kemampuan Pupuk Organik Cair Urine Sapi Dalam Mensubstitusi Penggunaan Pupuk Npk Pada Budidaya Jagung Manis (Zea mays L. saccharata) Konvensional - Nurseha Nurseha; Sri Mulatsih (University of Prof. Dr. Hazairin, SH, 2017)
This research aimed to know: a) influence of cow slurry organic fertiliser on growth and yield of sweet corn, b) best dosage level of cow slurry organic fertiliser on growth and yield of sweet corn to substiture NPK chemical fertiliser. This research used Randomized Blocked Design in single factor with six treatments and four replication. The results showed that 1) the application of cow slurry organic fertiliser made significant different on the growth and yield of sweet corn. 2) Application of 400 kg Urea per hectar (96 g/plot), 350 kg SP36 per hectar (84 g/plot) dan 100 kg KCl per hectar (24 g/plot) gave the best growth and yield of sweet corn. 3) Application of liquid organic fertiliser at 5000 l/ha was the most optimal for growth and yield of sweet corn compared to all other cow slurry dosage level.